Amplitude modulated Lorentz force MEMS magnetometer with picotesla sensitivity. (20th September 2016) - Kumar, Varun; Ramezany, Alireza; Mahdavi, Mohammad; Pourkamali, Siavash
Abstract: This paper demonstrates ultra-high sensitivities for a Lorentz force resonant MEMS magnetometer enabled by internal-thermal piezoresistive vibration amplification. A detailed model of the magneto-thermo-electro-mechanical internal amplification is described and is in good agreement with the experimental results. Internal amplification factors up to ~1620 times have been demonstrated by artificially boosting the effective quality factor of the resonator from 680 to 1.14  ×  10 6 by tuning the bias current. The increase in the resonator bias current in addition to the improvement in the quality factor of the device led to a sensitivity enhancement by ~2400 times. For a bias current of 7.245 mA, where the effective quality factor of the device and consequently the sensitivity is maximum (2.107 mV nT −1 ), the noise floor is measured to be as low as 2.8 pT (√Hz) −1 . This is by far the most sensitive Lorentz force MEMS magnetometer demonstrated to date.